2016
DOI: 10.18869/acadpub.joge.1.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of the implementation of physical activities in elderly in Tehran

Abstract: Introduction: Despite the importance of exercise and physical activity on the health of elderly, the amount o physical activity (exercise) among this vulnerable class of society is declining. This study was conducted with the aim of identifying the determinants of the implementation of physical activities in the older adults in Tehran.Method: This Study was a qualitative design and carried out using Grounded theory methodology. Data was collected via semi-structured in-depth interviews and field notes. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…[ 15 ] Women pointed out enjoying the participation in group physical activity as a motivator that should be paid attention to by organizational factors and policymakers in the domain of women exercise and health. These findings are consistent with the results of the studies by Nadri[ 16 ] and Amini. [ 17 ] Women viewed the lack of safety of the places of exercise in the city as a social obstacle for doing physical activity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…[ 15 ] Women pointed out enjoying the participation in group physical activity as a motivator that should be paid attention to by organizational factors and policymakers in the domain of women exercise and health. These findings are consistent with the results of the studies by Nadri[ 16 ] and Amini. [ 17 ] Women viewed the lack of safety of the places of exercise in the city as a social obstacle for doing physical activity.…”
Section: Discussionsupporting
confidence: 94%
“…However, negative attitudes of the family members and lack of accompanying women in physical activity, especially by the husbands, due to an inactive family lifestyle or family dogmatic beliefs indicative of the lack of women's exercise and sports culture in the family expressed as negative nurturers in the family for participation in exercise activities. These findings were consistent with the findings of the studies by Nadri,[ 16 ] Razmara,[ 25 ] and Shahbazi. [ 7 ] Communicating with diabetic families and individuals was also pointed out by women as a motivator for doing physical activity and this was also pointed out in the study by Shahbazi.…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that extrinsic motivation that stems from the environment can help older adults start PA, while intrinsic motivation is the key to success or long-term commitment to PA. 31 Future research about environmental issues is warranted because socio-cultural and environmental barriers such as air pollution and lack of safe public places, which can lead to fear of accident and injury, were acknowledged to have contributed to a decrease in older adults' PA in a sample of the Iranian population. 32 In terms of environmental issues, our study may also confirm the findings of another Iranian qualitative research study that explained how lack of autonomy (restrictions posed by others), lack of environmental safety, poor public transport, and inaccessibility to sport facilities played roles as motivational barriers to older adults' engagement in PA. 33 With a focus on education and motivation, the findings of this study suggest developing useful strategies that can be implemented by communities to improve external factors and empower older adults' interpersonal and community motivation for PA. Some strategies are providing free access to group-based exercise classes at senior facilities, raising awareness of the benefits of PA, and providing opportunities for social interaction through the construction of open spaces and attractive walking areas.…”
Section: Discussionmentioning
confidence: 92%
“…Despite all the aforementioned physical and mental benefits, lack of movement is quite prevalent among the elderly 22. Studies have shown that only 13.7% of the elderly are engaged in physical activities 23.…”
Section: Introductionmentioning
confidence: 99%
“…It is not easy to encourage the elderly to be more active. It has been reported that costs or lack of money, insufficient awareness of the benefits of physical activities, distance from gyms, transportation restrictions and dependence on others for getting around, and lack of time are among the main factors keeping the elderly from taking part in physical activities; and that gaining health, maintaining and improving physical fitness, pleasure and joy, social interactions, and controlling stress are among the top motivators for the elderly to engage in physical activities 22. Mouton et al made use of games to improve motion and physical activities in the elderly, and they observed that the elderly would gradually engage in exercise sessions with more independence and enthusiasm 25.…”
Section: Introductionmentioning
confidence: 99%